Integrating Chatgpt Into Teaching: Students’ Perceptions Of Its Usefulness And Reliability As A Pedagogical Resource - Sánchez-Labella, José; González-Rojas, Antonio; Pla Julián, Isabel (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The emergence of generative artificial intelligence in higher education presents both opportunities and pedagogical, ethical, and cognitive challenges. This study combines a recent theoretical review with empirical analysis involving Social Work students to explore the impact of ChatGPT on learning. Students especially valued its ability to structure information and facilitate specific tasks such as data searching or initial text drafting. However, some students expressed concerns about the accuracy of generated content, its influence on teamwork, and potential risks of dependency. Responses underscore ChatGPT’s potential as a professional support tool, while emphasizing the need for critical, ethical, and context-aware use. The study concludes with recommendations for a responsible integration of AI into universities, particularly in disciplines with a strong relational component such as Social Work.